Bicuspid valve repair outcomes are improved with reduction and stabilization of sinotubular junction and annulus with external annuloplasty - Shraer, Nathanael; Youssefi, Pouya; Zacek, Pavel; Debauchez, Mathieu; Leprince, Pascal; Raisky, Olivier; Lansac, Emmanuel (Journal of thoracic and cardiovascular surgery, 2024)
OBJECTIVE: We investigated long-term outcomes of bicuspid aortic valve (BAV) repair, with external annuloplasty, according to aorta phenotype. METHODS: Between 2003 and 2020, all patients with BAV operated on for aortic insufficiency (AI) and/or aneurysm were included. Repairs included isolated AI repair with subvalvular with or without sinotubular junction (STJ) (single or double) annuloplasty, supracoronary aorta replacement (with or without hemiroot remodeling), and root remodeling with external subvalvular ring annuloplasty. RESULTS: Among 343 patients operated, reparability rate was 81.3% (n = 279; age 46 ± 13.3 years). At 10 years (median follow-up: 3.42 years; interquartile range, 1.1, 5.8), survival was 93.9% (n = 8 deaths, similar to general population), cumulative incidence of reoperation was 6.2% (n = 10), AI grade >2 was 5.8% (n = 9), and grade >1 was 23.0% (n = 30). BAV repair stabilizing both the annulus and STJ with annuloplasty, compared with nonstabilized STJ repair (single annuloplasty), had lower incidence of reoperation (2.6% vs 22.5%, P = .0018) and AI grade >2 (1.2% vs 23.6%, P < .001) at 9 years. Initial commissural angle <160° was not a risk factor for reoperation, compared with angle ≥160° if symmetrical repair was achieved (2.7% and 4.1%, respectively, at 6 years, P = .85). Multivariable model showed that absence of STJ stabilization (odds ratio, 6.7; 95% confidence interval, 2.1-20, P = .001) increased recurrent AI, but not initial commissural angle <160° (odds ratio, 1.01; 95% confidence interval, 0.39-2.63, P = .98). Commissures adjusted symmetrically led to lower transvalvular gradient, compared with nonsymmetrical repair (8.7 mm Hg vs 10.2 mm Hg, P = .029). CONCLUSIONS: BAV repair, tailored to aorta phenotype, is associated with excellent durable outcomes if both annulus and STJ are reduced and stabilized with external ring annuloplasty. Commissural angle <160° is not associated with reoperation if symmetrical repair is achieved.
Keywords: výsledek terapie; anuloplastika srdeční chlopně; bikuspidální aortální chlopeň; Aortic Valve Insufficiency; Male; Postoperative Complications; retrospektivní studie; Risk Factors; Bicuspid Aortic Valve Disease; Heart Valve Prosthesis Implantation; Adult; dospělí; mužské pohlaví; pooperační komplikace; Cardiac Valve Annuloplasty; aortální chlopeň; chirurgická náhrada chlopně; aortální insuficience; Treatment Outcome; Time Factors; aortální aneurysma; Aortic Valve; lidé; ženské pohlaví; Humans; Aortic Aneurysm; časové faktory; rizikové faktory; Reoperation; Retrospective Studies; Female; lidé středního věku; reoperace; Middle Aged